The formation of hemp (Cannabis sativa L.) yield capacity depending on the sown areas weed infestation - Ovsianyk, O.; Marenych М. (Scientific Progress & Innovations, 2025)
Hemp is a crop, which requires the diligently developed cultivation technology without considering its unique adaptive ability and competition with weeds as well as resistance to unfavorable cultivation factors. The analysis of theoretical material has shown that there is a considerable lack of data and scientific results. In Ukraine, a limited amount of herbicides for applying on hemp is available; therefore the topicality of the research is undoubted, as some preparations may have a considerable negative effect on the crop itself. In connection with all the above mentioned, the purpose of the paper was to find the peculiarities of hemp seed and straw yield formation depending on weed infestation and using the rates of herbicides to control their amount. The studies were conducted with Glesia, Sofia, and Gliana hemp varieties in “Olyshivka” LLC of Chernihiv region. To make the experiment, Gesagard, Stomp and Senkor Liquid herbicides were used. It was found that the use of minimal rates of Gesagard (1.5 l/ha), Stomp (1.5 /ha), and Senkor Liquid (0.3 l/ha) herbicides favored the increase in seed yield by 0.12–0.20 t/ha in comparison with the control, where the herbicides were not applied. Straw yield grew considerably less; however the increase to 8 % was statistically reliable. The highest straw yield was fixed on the variants when using Senkor Liquid (metribuzin, 600 g/l) in the rates of 0.3 l/ha and 0.5 l/ha. The increase in the preparation application rate to 0.75 l/ha caused the decrease in the straw yield by 0.1 t/ha. Such results are explained by the dependence between the amount and weight of segetal plants and hemp yield capacity – the unfavorable effect of weeds on seed yield in hemp agro-ecosystem was characterized by a strong negative correlation – r = –0.72, and on straw yield it was somewhat lower and made r = –0.57. It has been found that the main factor, which affects the yield formation, was the conditions of cultivation years – moisture deficit against the background of high temperatures caused almost the double seeds yield decrease. However, the straw yield increase was observed.